Choosing between supermarkets and wet markets - Raneri, Jessica; Wertheim-Heck, Sigrid (2019)
Food safety and better nutrition are real and serious challenges facing billions of people in low- and middle-income countries worldwide in urban and rural settings. Addressing both these issues are critical to achieve our Sustainable Development Goals, particularly those related to ending hunger. But they compete for attention, priority and resources from governments and consumers and people involved throughout the food system. Moreover, sometimes, actions taken to improve one objective occur at the expense or detriment of the other.